GROWTH OF BANGKOK CHICKEN (Gallus sp) WITH DIFFERENCES IN FOOD TYPES - RAHMADINA RAHMADINA (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2019)
This study aims to determine the development Siyam Bangkok chicken (Gallus sp) against three different types of food, such as rice, corn, and BR. This study uses three Siyam Bangkok chickens (Gallus sp), which are kept in a different order to more easily differentiate chickens that were fed rice, corn and BR. From the observed bangkok chicken (Gallus sp) eat rice slower growth than in chickens eat corn and BR. Regular feeding will also affect the growth of Siyam bangkok chicken (Gallus sp). The results of the research conducted at Siyam bangkok chicken (Gallus sp) eat BR growth is better and bigger than Siyam bangkok chicken (Gallus sp) who ate rice and corn.